Perepresentasian Liyan Dalam Novel Ushfur Min Ash-Sharq Karya Tawfiq Al-Hakim - Apriyono, Hendra (Adabiyyāt: Jurnal Bahasa dan Sastra, 2020)
This research is motivated by the imbalance of relations between East and West in Arabic travel literature. The inequality is caused by the representation of the superior (West) and the inferior (East) which is constantly being produced. The novel Uṣfur min al-Syarq by Taufiq al-Hakim as one of Arabic travel literature is considered to offer a different view from other Arabic travel literature by proposing the value of equality between East and West. This research is expected to be able to resolve the problem of inequality in relations between East and West as represented in Arabic travel literature. This research uses another representation strategy from Carl Thompson's travel literary concept which consists of colonial, neo-colonial, and post-colonial strategies. The results of this study found that the representations of the others made by al-Hakim which were dominated by the use of colonial and post-colonial strategies showed that the author occupied two opposing positions. On the one hand, al-Hakim is still trapped in colonial discourse and on the other hand, al-Hakim is not entirely successful in bringing the post-colonial travel agenda to escape from Western hegemony. The equality proposed by al-Hakim regarding the East is inseparable from Western assistance. To realize the equality of the East and the West, al-Hakim used the superiority of the West to face the West in order to defend the East.